The future of globalization explorations in light of recent turbulence - Zedillo Ponce de León, Ernesto (London Routledge, 2008)
Erudite and topical, this well balanced treatment, with essays from world renowned contributors including the former President of Ireland ? Mary Robinson, Jagdish Bhagwati and Nobel prize winner Joseph Stiglitz, considers the forces that propel globalization and those that resist it. Local and regional experiences from Bangladesh, China, India, Latin America and the Middle East are analyzed along with some of globalization?s most potent risks.
Includes bibliographical references and index.
Keywords: Globalization --Economic aspects